Revision of G. Evans’ interpretation of Fregean Semantic Theory (Evan’s ’Frege’ Revisited) - Trigos Carrillo, Lina Marcela (Estudios de Filosofía, 2012)
The first chapter of The Varieties of Reference by Gareth Evans, called ‘Frege’, opens the doors to new perspectives for the analysis of Fregean Theory. This paper aims to revisit Evans’ interpretation of Fregean Semantic Theory, to analyze some of the consequences derived from such interpretation, and to propose a version of Fregean Semantic Theory that can account for the problematic cases in the analysis of a Natural Language. This paper is divided in two major parts: in the first eight minor parts, Evans´ argument is reconstructed and analyzed; and in its conclusions, there is an analysis of the conclusions reached by Evans bearing on his argument and there is a proposal to make compatible the Compositionality Principle and the Context Principle in the Fregean frame with the intention of solving conflictive cases for a Fregean Semantic Theory of Natural Language.